Navigating Rough Waters: Global Shipping and Challenges for the North Range Ports - Jan Wedemeier; Lukas Wolf (Intereconomics)
Abstract Ports and shipping have been in the spotlight in 2021 with surging demand, skyrocketing freight rates and week-long queues. This development stands against the background of the current global COVID-19 pandemic. Amid these disruptive waves, the North Range ports (Le Havre to Hamburg) face numerous challenges. This short analysis gives an overview of recent developments in international shipping and the potential for maritime transport as an early indicator for commodity trade. The article also explores the connection in import and export of the North Range ports to their respective countries and the EU. This article contributes to the extent to which maritime traffic data can be linked to economic data. Three long-term key challenges — sustainability, digitalisation and (de)globalisation — are discussed with a focus on the North Range ports as well as the newest effects of Russia’s war in Ukraine.